Heaney and education. Issue 4 (2nd October 2017) - Jones, Sharon
Abstract: Seamus Heaney inhabited the world of teacher education, as a student, and later as a lecturer, in 1960s Belfast. That world was infused by three ideas: learning as a journey, learning through play, and learning as construction. This article traces correspondences between these and thematic trends in Heaney's work. It presents the case that Heaney's writing reflects an informed understanding of children and of learning peculiar to the mind of a great teacher. Moreover, Heaney's contribution to education is remarkable in that it transcends the school and the academy, and offers a creative vision in which poetry and learning are inextricably linked. As Heaney put it in Among Schoolchildren, the "walls of the world expand" as reader and writer, teacher and learner, poet and child "go beyond our normal cognitive bounds and sense a new element where we are not alien but liberated, more alive to ourselves, more drawn out, more educated".